2018
DOI: 10.1007/s00521-018-3765-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Deep Improviser: a prototype deep learning post-tonal free music generator

Abstract: Two modest-sized symbolic corpora of post-tonal and post-metrical keyboard music have been constructed, one algorithmic, the other improvised. Deep learning models of each have been trained. The purpose was to obtain models with sufficient generalisation capacity that in response to separate fresh input seed material, they can generate outputs that are statistically distinctive, neither random nor recreative of the learned corpora or the seed material. This objective has been achieved, as judged by k-sample An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As an important part of music information retrieval, music emotion classification based on audio has attracted more and more attention. The second-level emotional expression in national vocal music mainly refers to the singer's realization of the emotional state through deeper excavation, such as through sound, expression, and movement form [15]. The article builds the model shown in Fig.…”
Section: Analysis and Implementation Of National Music Deep Learning ...mentioning
confidence: 99%
“…As an important part of music information retrieval, music emotion classification based on audio has attracted more and more attention. The second-level emotional expression in national vocal music mainly refers to the singer's realization of the emotional state through deeper excavation, such as through sound, expression, and movement form [15]. The article builds the model shown in Fig.…”
Section: Analysis and Implementation Of National Music Deep Learning ...mentioning
confidence: 99%
“…Briot et al (2017) built a value music style automatic learning and generation model based on the deep learning, and found that deep learning algorithms can automatically generate music without human interaction, but there were still some problems of control, creativity, and interaction [17]. Dean et al (2018) applied deep learning to generate music, and found that the synthesized music was roughly the same as the example [18]. Zhu et al (2020) constructed a multiinstrument collaborative arrangement model by using the deep learning and multi-task learning methods, and verified the superiority and effectiveness of the model on real data sets [19].…”
Section: A Application Progress Of Deep Learning In Arrangementmentioning
confidence: 99%
“…Recently, deep learning [20][21][22][23] has shown a remarkable performance in extraction and expression of the effective features and inherent mapping relationships in high-dimensional state space. Compared with the traditional neural network, deep learning can extract the inherent features between adjacent states, learn inherent mapping relationships of the system state-action space, and describe the nonlinear process well.…”
Section: Introductionmentioning
confidence: 99%